1970
DOI: 10.1111/j.1600-0722.1970.tb02091.x
|View full text |Cite
|
Sign up to set email alerts
|

Postural activity in the muscles of mastication with the subject upright, inclined, and supine

Abstract: With the mandible at rest, electromyographic recordings were obtained from the anterior temporal, lateral pterygoid, and digastric muscles with the subjects (A) sitting upright with the head unsupported, (B) inclining backwards with the back-rest at an angle of 45", and (C) supine. Two minutes after a shift in posture the electrical activity in the anterior temporal muscles was strongest in the upright position, it decreased slightly when the back-rest was at 45", and was least in the supine position. The diga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
6

Year Published

1978
1978
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 5 publications
2
36
0
6
Order By: Relevance
“…The activity in the lateral pterygoid muscles is maximal at an angle of 450 to the vertical axis. The temporal and digastric muscles are more active when the subject's head is vertical (Lund et al, 1970). This explains why it has been suggested that the centric relation should be recorded with the patient lying down (Eberle, 1951).…”
Section: 4) Physiological Mechanisms Controlling the Centric Relationmentioning
confidence: 88%
See 2 more Smart Citations
“…The activity in the lateral pterygoid muscles is maximal at an angle of 450 to the vertical axis. The temporal and digastric muscles are more active when the subject's head is vertical (Lund et al, 1970). This explains why it has been suggested that the centric relation should be recorded with the patient lying down (Eberle, 1951).…”
Section: 4) Physiological Mechanisms Controlling the Centric Relationmentioning
confidence: 88%
“…This explains why it has been suggested that the centric relation should be recorded with the patient lying down (Eberle, 1951). However, in all cases, the differences in the EMG measurements taken while the patient was sitting or lying down are small (Lund et al, 1970), and no difference has been found in centric relation values between the two positions (Tripodakis et al, 1995). In summary, it seems that gravity, and therefore the position of the head relative to the vertical axis, has little relevance to the clinical determination of the centric relation.…”
Section: 4) Physiological Mechanisms Controlling the Centric Relationmentioning
confidence: 95%
See 1 more Smart Citation
“…17 Lund et al 17 reported that when the mandible remained in the resting position for longer periods of time, a change occurred in the electromyographic activity of the masseter and temporalis muscles. Such results are in agreement with the ones obtained in this study, in which the re-programming device changed the electromyographic activity during the specified time period; however, the data were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that surface EMG recordings were influenced by location of the electrodes over the muscle, inter-electrode distance, body posture and psychological factors [25][26][27]. The electrode location has a large influence especially on characteristics of the recorded EMG signal.…”
Section: Effect Of Location In the Surface Emg Recordingmentioning
confidence: 99%